DZIKIR KHAFI UNTUK MENURUNKAN TINGKAT KECEMASAN PADA LANSIA - Mujib Hannan (Wiraraja Medika : Jurnal Kesehatan, 2014)
Many elderly experiences the condition had been developed in the form of changes that lead to negative changes diantaranyanya feel anxious if complaints recurred. Anxiety is an uncomfortable sense as a form of manifestation of a sense of fear of losing something important or the occurrence of adverse events and conditions. Khafi Dhikr can be used nurses as nursing interventions to meet the problems of anxiety, which with the dhikr of Allah SWT in the period that is not too long, will give you peace, remembrance arises through the sense of grandeur and beauty pendahiran Allah. Objective: Knowing the silent dhikr to lower the level of anxiety in the elderly in the village Saronggi.47This research is aquasi experimentwithusingdesignControl GroupPretestPost test. The populationisthe entireelderlyMuslimwhohadlivedin the village ofanxietySaronggiby 47seniors. Sampling techniqueby purposive samplingbased oninclusion and exclusion criteriafor 34elderly. Analysis techniques were todetermine differences inanxietylevelsbeforeand aftertreatmentusinga non-parametric testWilcoxon testt-test with aconfidenceinterval of95%.The results of the study the majority of respondents are experiencing anxiety before treatment is given Khafi Dhikr of 61.8%, and the majority of respondents experiencing mild anxiety after treatment Dhikr Khafi given by 44.1%. There berbedaan tingka anxiety before and after the treatment Dhikr Khafi ie decrease anxiety levels before and after the Dhikr Khafi in the elderly. The conclusion of this study is Dhikr Khafi effective to reduce the level of anxiety in the elderly Keywords: DzikirKhafi, AnxietyLevels, Elderly